Pengaruh Budaya Organisasi, Lingkungan Sekolah, dan Kepemimpinan Kepala Sekolah Terhadap Kepuasan Kerja Tenaga Pendidik dan Kependidikan di SMA Swasta Adhyaksa Ende - Lengo, Leonardus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
To analyze the influence of organizational culture, school environment, and leadership on job satisfaction of Adhyaksa High School teachers. This research includes quantitative research. The sample in this study were 34 educators and education personnel at 27 Adhyaksa Ende High School. Data were collected by distributing questionnaires that had been tested for validity and reliability. The results of this study indicate that first, there is no significant influence of organizational culture on job satisfaction, second, there is an influence of the school environment on job satisfaction, and finally there is an influence of leadership on job satisfaction. Organizational culture, school environment and leadership have a significant effect on job satisfaction of educators and education personnel of Adhyaksa Ende Private High School. This finding indicates that the increase in organizational culture, work / school and leadership will further increase the job satisfaction of educators and education personnel of Adhyaksa Ende Private High School.